Adaptation and Feasibility Study of a Digital Health Program to Prevent Diabetes among Low-Income Patients: Results from a Partnership between a Digital Health Company and an Academic Research Team - Valy Fontil; Kelly McDermott; Lina Tieu; Christina Rios; Eliza Gibson; Cynthia Castro Sweet; Mike Payne; Courtney R. Lyles (Journal of Diabetes Research)
Background. The feasibility of digital health programs to prevent and manage diabetes in low-income patients has not been adequately explored. Methods. Researchers collaborated with a digital health company to adapt a diabetes prevention program for low-income prediabetes patients at a large safety net clinic. We conducted focus groups to assess patient perspectives, revised lessons for improved readability and cultural relevance to low-income and Hispanic patients, conducted a feasibility study of the adapted program in English and Spanish speaking cohorts, and implemented real-time adaptations to the program for commercial use and for a larger trial of in multiple safety net clinics. Results. The majority of focus group participants were receptive to the program. We modified the curriculum to a 5th-grade reading level and adapted content based on patient feedback. In the feasibility study, 54% of eligible contacted patients expressed interest in enrolling (n=23). Although some participants’ computer access and literacy made registration challenging, they were highly satisfied and engaged (80% logged in at least once/week). Conclusions. Underserved prediabetic patients displayed high engagement and satisfaction with a digital diabetes prevention program despite lower digital literacy skills. The collaboration between researchers and a digital health company enabled iterative improvements in technology implementation to address challenges in low-income populations.